FRI0294 MUSCULOSKELETAL MANIFESTATIONS IN PATIENTS WITH INFLAMMATORY BOWEL DISEASE TREATED WITH VEDOLIZUMAB. (13th June 2020) - Rodríguez-Merlos, P.; Ruiz- Ramirez, M. A.; Plasencia, C.; Navarro-Compán, V.; Suarez-Ferrer, C.; Martin-Arranz, E.; Martín Arranz, M. D.; Peiteado, D.; Bonilla, G.; Sánchez Azofra, M.; Poza Cordón, J.; Franco Gomez, K. N.; et al.
Abstract : Background: Musculoskeletal manifestations (MEM) are frequent extraintestinal symptoms in patients suffering from inflammatory bowel disease (IBD), affecting up to 40% of them. Tumor necrosis factor inhibitors (TNFi) are effective in both IBD and IBD-related spondylarthritis (SpA). Additionally, vedolizumab (VDZ), an α4β7 integrin inhibitor with selective action on intestinal tissue, has been recently proposed as 1st line treatment on TNFi refractory IBD. The effectiveness of VDZ in MEM has not been properly evaluated but even exacerbation of previously diagnosed SpA has been described. Objectives: The main objective is to analyse the occurrence of articular exacerbations in patients with IBD-related SpA treated with VDZ. The secondary objective is to analyse the new-onset MEM in IBD patients treated with VDZ. Methods: Descriptive study of a retrospective cohort of every adult with IBD (Crohn's disease -CD- and ulcerative colitis -UC-) patients starting treatment with VDZ in a tertiary hospital. All data were collected as a collaboration between the Rheumatology and Gastroenterology Departments, through revision of the clinical history and databases from both departments. In patients previously diagnosed of SpA exacerbation was assessed, defined as a clinical worsening causing a treatment modification. The patients with new-onset MEM were classified as: i) nonspecific arthralgia (NsA), not suggestive of SpA; and ii) SpA according to ASAS criteria. A statistical analysis was performed using frequency charts Results: A total of 61 patients were included, 55.7% women and with an mean (SD) age of 50 (17) years. The proportion of UC and CD was similar (49% and 51%, respectively). Among the patients studied, 12 (19.7%) had a diagnosis of IBD-related SpA and 3 (25%) of them suffered articular exacerbation of SpA within 3, 5 and 6 months of treatment. On the other hand, 9 (14.7%) patients showed new-onset MEM, 3 (33%) of them showed symptoms and clinical and/or radiological findings compatible with axial SpA. In 2 of the cases a treatment with a cDMARD was used and the other one required a combination therapy between iTNF and VDZ. The remaining 6 (67%) patients were classified as NsA and inflammatory arthritis was discarded. Table 1 shows the demographic and clinical characteristics of patients included in the analysis. Conclusion: Switching TNFi treatment to VDZ in patients with IBD-related SpA was found to be associated with articular exacerbation of SpA in 1 out of 4 patients within the first 5 months. New-onset MEM is also observed in up to 15% of patients with IBD treated with VDZ. A multidisciplinary assessment of these patients is necessary in order to achieve a proper management of their diseases. Disclosure of Interests: Pablo Rodríguez-Merlos: None declared, MARIA ANGELES RUIZ- RAMIREZ: None declared, Chamaida Plasencia: None declared, Victoria Navarro-Compán Consultant of: Abbvie, Lilly, Novartis, Pfizer, UCB, Speakers bureau: AbbVie, MSD, Lilly, Novartis, Pfizer, UCB, Cristina Suarez-Ferrer: None declared, Eduardo Martin-Arranz: None declared, Maria Dolores Martín Arranz: None declared, Diana Peiteado: None declared, Gemma Bonilla: None declared, María Sánchez Azofra: None declared, Joaquín Poza Cordón: None declared, Karen Nathalie Franco Gomez: None declared, Alejandro Balsa Grant/research support from: BMS, Roche, Consultant of: AbbVie, Gilead, Lilly, Pfizer, UCB, Sanofi, Sandoz, Speakers bureau: AbbVie, Lilly, Sanofi, Novartis, Pfizer, UCB, Roche, Nordic, Sandoz